Mid-Late Pleistocene benthic foraminifera from Southwestern South Atlantic: driven by primary productivity or water mass properties? - García Chapori, Natalia Luz; Laprida, Cecilia; Watanabe, Silvia; Totah, Violeta Ines; Violante, Roberto Antonio
In the Atlantic sector of the Southern Ocean up to 35°S, Neogene benthic foraminiferal faunal changes have been interpreted, alternatively, as changes in deep water-masses distribution and organic matter availability. In surface, the Southwestern South Atlantic presents a highly dynamic frontal zone and exhibits large spatial and temporal variability in primary productivity that influences the export of organic carbon from the euphotic zone. However, below ~1000 meters depth, it is characterized by the interaction of several water masses. For this reason, the western sector of the South Atlantic is a natural laboratory to test the benthic foraminifera’s response to changes in both, the deep water-masses distribution and the exported productivity. In order to define which was the main factor controlling the benthic foraminiferal assemblages structure during a glacial Mid-Late Pleistocene event, abundance analysis of organic matter content, oxygen availability and water masses marker species, and Q-mode factor analysis were carried out on core SP1251 (3400m; ~38°S - 54°W). Our results indicate that the benthic foraminiferal assemblages are mainly composed of high organic matter and oxygen availability-associated species revealing that productivity has been the main factor in determining the structure of the assemblages’composition. These results also reflect that surface productivity regime would have not been uniform as a result of variations in the shelfbreak upwelling of Patagonia as a consequence of variations in the Antarctic upwelling. Fil: García Chapori, Natalia Luz. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos Argentina Fil: Laprida, Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de ...